2013
DOI: 10.1108/jcre-01-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustainable office buildings on occupant's comfort and productivity

Abstract: Purpose -The purpose of this paper is to research the impact of sustainable office buildings on occupant's comfort and self-assessed performance and work engagement. Design/methodology/approach -The research consists in an empirical study of 18 office buildings and is based on survey data from almost 1,500 employees. Findings -The study shows that the building itself has a clear impact on the comfort level of the building user. Also, the positive impact of certain features, such as operable windows and the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
136
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 40 publications
0
136
0
7
Order By: Relevance
“…As noted by Feige et al (2013) measuring performance and productivity in the commercial office environment can be challenging and often indirect measures such as absenteeism, staff turnover etc. may be used, alternatively self-reported productivity (occupant survey) may be employed.…”
Section: Methodsologymentioning
confidence: 99%
See 3 more Smart Citations
“…As noted by Feige et al (2013) measuring performance and productivity in the commercial office environment can be challenging and often indirect measures such as absenteeism, staff turnover etc. may be used, alternatively self-reported productivity (occupant survey) may be employed.…”
Section: Methodsologymentioning
confidence: 99%
“…According to Feige et al, (2013) worker performance can be linked to productivity, but both are rarely measured in the workplace, which can prove especially difficult where there is no universally accepted measure of office productivity (Haynes, 2008a). It is instead suggested that measuring self-reported subjective productivity through questionnaires may be appropriate (Haynes, 2008b;Feige et al, 2013).…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…To give two examples of over-provision to satisfy assumed needs, firstly there is the almost universal use of use of four-pipe fan-coil unit air-conditioning systems in 'Grade A' offices (see below) to deal with large imagined potential cooling needs. This was not justified primarily in terms of ventilation and its link with productivity (lower-energy ventilation systems can anyway deliver adequate fresh air; Cao et al, 2014;Feige, Wallbaum, Janser, & Windlinger, 2013), but in terms of it providing 'flexibility' to unknown and therefore potentially high 'needs'. Secondly, the provision of capacity for occupiers to extract large amounts of 'small power' (the UK term for plug loads, or power demanded by occupiers' appliances and devices; Menezes, Cripps, Buswell, Wright, & Bouchlaghem, 2014) exceeds the loads regulated under the building's EPC ratings (Arup, 2013), and has consistently exceeded users' empirical needs (British Council for Offices, 2009, 2014).…”
Section: Speculative Design For Unknown Future Usersmentioning
confidence: 99%